PENGARUH IMPLEMENTASI SISTEM INFORMASI KRU, KEDISIPLINAN KRU DAN MANAJEMEN ARSIP KRU TERHADAP PERFORMA KRU KAPAL (Studi pada kru kapal PT. Tavia Digital Solusi) - Abdullah Muksin; Syaiful Anwar (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of Management Information Systems, Discipline and archives manajement on crew performance on ship crew employees at PT. Tavia Digital Solutions South Jakarta. This research is a quantitative research with a sample size of 47 respondents. The sampling method uses probability sampling with a simple random sampling technique using the Slovin formula. The data collection technique is through a questionnaire with a Likert scale which has been processed using Microsoft Excel 2019 software and SPSS software version 26. Data analysis used is validity and reliability testing, classical assumption testing, hypothesis testing and multiple linear regression. The results of this research show that the Management Information System and Discipline variables have a positive and significant effect on Crew Performance. Meanwhile, the Records Management variable does not have a significant effect on Crew Performance. It is hoped that the results of this research can provide a managerial contribution to efforts to improve crew performance at PT. Tavia Digital Solutions